(3GdQSGdI GdbTjQjIs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO agPg WHbI eTGjN Cgd GdMbjbI , PcQgG GdTjN GdEeGe GdYGQa YHO GdcQje Hf ghGRf GdbTjQi ai ChGFd cJGHI GdQSGdI , abGd QMeg Gddg (B: (3HGH ai PcQ eTGjN gPg GdWQjbI s
(3BNQgG (B:s
(3hCeG GdeTGjN GdPjf COQcfGge adh ETJZdfG HPcQge , hJbUjd CMhGdge , dNQLfG Yf GdebUhO ai GdEjLGR hSjeQ ef NWGHGJge WQa ai ehGVY ef gPg GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQi bSe GdJQGLes
(3cJHJ CSeGA GdeJQLejf HGdMeQI Ydi GdgGeT s
(3YdjgG Jedc HGSe eMeO Hf LGQ Gddg Hf agO GdgGTei Ke hba GdSjO MSjf Hf Sgd Ydi JQje hfhGMjgG SfI (B1275(3g` s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs